Drumstick (Moringa oleifera) variation in biomass and total flavonoid content in Indonesia - Ridwan RIDWAN; Hamim Hamim; Suharsono SUHARSONO; Nuril Hidayati; INDRA GUNAWAN (Society for Indonesian Biodiversity, 2021)
Abstract. Ridwan, Hamim, Suharsono, Hidayati N, Gunawan I. 2021. Drumstick (Moringa oleifera) variation in biomass and total flavonoid content in Indonesia. Biodiversitas 22: 493-500. Utilization of a drumstick (Moringa oleifera Lam.) leaf has recently increased worldwide which consequently cause the increase in global demand. Indonesia, as a tropical country with large area, has a great potential to become a center for drumstick cultivation and leaf production. Drumstick distribution scattered in almost all of the islands of Indonesia has another potential for obtaining superior genotype variabilities. The aim of this study was to select the drumstick accessions from several islands in Indonesia with high leaf biomass production and flavonoid content. This experiment was carried out in the field using ten accessions of drumstick from ten islands in Indonesia, namely Sumatra, Java, Madura, Bali, Lombok, Sumbawa, Sumba, Kalimantan, Sulawesi, and Papua. Drumstick seeds were planted in polybags with a capacity of 10 kg and arranged using a randomized block design with three replications. The parameters observed were plant growth, biomass production, total flavonoid content, and antioxidant activity. The results of this study found that Sumatra accession was the accession which had the highest leaf biomass production in combination with the uppermost total flavonoid content and antioxidant activity compared to others. Sumatra accession is recommended as an excellent accession for cultivation with the aim of producing flavonoids.